THE ASCENDANCY OF THE SILICON ALCHEMIST: A COMPREHENSIVE ANALYSIS OF AI TOOLS IN CHEMISTRY WITH IMPLEMENTATION DETAILS - Gapurov U.U.,; Safarova N.S., (Journal of new century innovations, 2024)
Abstract: nowadays machine learning tools are being used effectively in wide range of science fields as well as in Chemistry. AI is in great help of ranging from predicting reaction pathways of new organic synthesis to calculating quantum chemical properties of novel substances[1-8]. Chemistry, the grand tapestry woven from the intricate interplay of atoms and molecules, has historically thrived on the keen intuition and meticulous experimentation of its practitioners. However, a revolutionary force is emerging within the hallowed halls of the laboratory – Artificial Intelligence (AI). This comprehensive analysis delves into the burgeoning field of AI in chemistry, illuminating its transformative applications, the profound benefits it bestows, and a captivating glimpse into its potential future.